Historical Theology An Introduction to the History of Christian Thought - McGrath, Alister E. (Maiden Blackwell Publishers, 1998)
This textbook introduces students to the study of theology from an historic point of view. Building on the chapters in "Christian Theology: An Introduction", it expands the content by including case studies which allow readers to engage more fully with a
Keywords: Theology -- History. Théologie -- Histoire. Theology